Metabolomics as a potential tool for monitoring patients with aneurysmal subarachnoid hemorrhage - Lasica, Nebojsa; Raicevic, Vidak; Stojanovic, Nikola M.; Djilvesi, Djula; Horvat, Igor; Jelaca, Bojan; Pajicic, Filip; Vulekovic, Petar (Frontiers in Neurology, 2023)
Metabolomics has evolved into a particularly useful tool to study interactions between metabolites and serves as an aid in unraveling the complexity of entire metabolomes. Nonetheless, it is increasingly viewed as a methodology with practical applications in the clinical setting, where identifying and quantifying biomarkers of interest could prove useful for diagnostics. Starting from a concise overview of the most prominent analytical techniques employed in metabolomics, herein we present a review of its application in studies of brain metabolism and cerebrovascular diseases, paying most attention to its uses in researching aneurysmal subarachnoidal hemorrhage. Both animal models and human studies are considered, and metabolites identified as potential biomarkers are highlighted.